Method for manufacturing a part having a welded seam from a nickel-chromium-aluminum alloy
Patent Information
- Application Number
- JP2024553736
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-10
- Filing Date
- 2023-03-03
- Publication Date
- 2025-03-26
Smart Images

Figure 2025508575000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing components having weld seams from a wrought nickel-chromium-aluminum alloy having excellent high-temperature corrosion resistance, good creep resistance and good workability.
[0002] Wrought austenitic nickel-chromium-aluminium alloys with different nickel, chromium and aluminium contents have long been used in furnace construction and in the chemical and petrochemical industries, where good high temperature corrosion resistance is required and good high temperature strength / creep resistance is required in carburizing atmospheres which cause "metal dusting".
[0003] In general, it should be noted that the hot corrosion resistance of the alloys shown in table 1 improves with increasing chromium content. All these alloys form a chromium oxide layer (Cr2O3) and a more or less closed aluminum oxide layer (Al2O3) below with the corresponding aluminum content. Small additions of elements with a strong oxygen affinity, such as yttrium or cerium, improve the oxidation resistance. The chromium content is gradually consumed in the formation of the protective layer in the course of use in the area of use. Therefore, the higher the chromium content, the longer the service life of the material. Because the higher the content of the chromium element forming the protective layer, the later the point at which the chromium content falls below the critical value and oxides other than pure chromium oxide (Cr2O3) are formed, which can be, for example, iron- or nickel-containing oxides. A further improvement in hot corrosion resistance can be achieved by the addition of aluminum and silicon. From a certain minimum content, these elements form a closed layer below the chromium oxide layer, thereby reducing the consumption of chromium.
[0004] In carburizing atmospheres (CO, H2, CH4, CO2, H2O mixtures, possibly with further non-oxidizing components due to the process), carbon penetrates into the material, which can lead to the formation of internal carbides. This causes a decrease in the notched impact strength. The melting point is also reduced to very low values (up to 350°C) and transformation processes can occur due to the depletion of chromium in the base material.
[0005] High carburization resistance is achieved by materials with low carbon solubility and low carbon diffusion rates. Nickel alloys are therefore generally more resistant to carburization than iron alloys, since both carbon diffusion and carbon solubility are lower in nickel than in iron. An increase in chromium content leads to high carburization resistance due to the formation of a protective chromium oxide layer, unless the oxygen partial pressure in the gas is too low for this layer to form. If the oxygen partial pressure is very low, materials containing silicon or aluminum can be used, which form layers of silicon oxide and aluminum oxide, which are formed at significantly lower oxygen partial pressures compared to chromium oxide, and which are more stable.
[0006] "Metal dusting" can occur in nickel, iron or cobalt alloys when the carbon activity is greater than 1 (i.e. the gas is not in equilibrium). When in contact with the gas, the alloy picks up large amounts of carbon. Segregation processes occurring in carbon-supersaturated alloys lead to material failure. The alloy then breaks down into a mixture of metal particles, graphite, carbides and / or oxides. This type of material failure occurs in the temperature range of about 500-750 °C.
[0007] A typical occurrence of "metal dusting" is a strongly carburizing gas mixture of CO, H2 and / or CH4, such as occurs especially in ammonia synthesis, methanol plants, metallurgical processes and even heat treatment furnaces.
[0008] "Metal dusting" resistance tends to increase as the nickel content of the alloy increases, but even nickel alloys do not offer resistance to "metal dusting."
[0009] The chromium and aluminum content have a significant effect on the corrosion resistance under "metal dusting" conditions (see Figure 2). Nickel alloys with low chromium content, such as Alloy 600 (N06600) alloy (see Table 1), exhibit relatively high corrosion rates under "metal dusting" conditions. Nickel alloys with a significantly higher corrosion resistance are Alloy 602 CA (N06025) nickel alloys with 25% chromium and 2.3% aluminum, and Alloy 690 (N06690) nickel alloys with a chromium content of 30% (Hermse, CGM and van Wortel, JC: Metal dusting: relationship between alloy composition and degradation rate. Corrosion Engineering, Science and Technology 44 (2009), p. 182-185). The higher the sum of chromium and aluminum (Cr+Al), the higher the "metal dusting" resistance.
[0010] At the nominal temperature (approximately 500-750°C), high temperature strength and creep strength are improved, especially with higher carbon contents. However, high contents of solution strengthening elements such as chromium, aluminum, silicon, molybdenum and tungsten also improve high temperature strength and creep strength. In the range 500-900°C, additions of aluminum, titanium and / or niobium may improve strength through precipitation of gamma- and / or gamma-inch phases.
[0011] Examples of these prior art alloys are listed in Table 1.
[0012] It has long been known that alloys such as Alloy602 CA (N06025), Alloy693 (N06693) or Alloy603 (N06603) have superior corrosion resistance compared to Alloy600 (N06600) or Alloy601 (N06601) due to their high aluminum content (>1.8%). Alloy602 CA (N06025), Alloy693 (N06693), Alloy603 (N06603) and Alloy690 (N06690) exhibit superior carburization and "metal dusting" resistance due to their high chromium and / or aluminum content. At the same time, alloys such as Alloy602CA (N06025), Alloy693 (N06693) or Alloy603 (N06603) have excellent high-temperature and creep strengths in the temperature range where "metal dusting" occurs due to their high carbon and aluminum contents. Alloy602CA (N06025) and Alloy603 (N06603) still have excellent high-temperature and creep strengths even at temperatures above 1000 °C. However, the workability is impaired, especially due to the high aluminum content, and the impairment is greater the higher the aluminum content (Alloy693-N06693). The same applies to silicon, which forms a low-melting phase with nickel. The high proportion of primary carbides in Alloy602 CA (N06025) or Alloy603 (N06603) limits the cold formability in particular.
[0013] WO 2013 / 182177 discloses a chromium content of 24-33%, aluminum content of 1.8-4.0%, iron content of 0.10-7.0%, silicon content of 0.001-0.50%, manganese content of 0.005-2.0%, titanium content of 0.0002-0.05%, magnesium and / or calcium content of 0.005-0.12%, carbon content of 0.001-0.050%, nitrogen content of 0.0001-0.020%, oxygen content of 0.001-0.030%, phosphorus content of 0.010%, sulfur content of 2.0%, molybdenum content of 2.0%, tungsten content of 2.0%, balance nickel and normal process impurities, where the following relationships must be satisfied: Cr+Al≧28 (2a) and Fp≦39.9 (3a), where Fp=Cr+0.272*Fe+2.36*Al+2.22*Si+2.48*Ti+0.374*Mo+0.538*W11.8*C (4a), Cr, Fe, Al, Si, Ti, Mo, W and C are the concentrations of the corresponding elements in weight percent. This nickel-chromium-aluminum alloy exhibits excellent high temperature corrosion resistance under highly corrosive conditions, such as excellent "metal dusting" resistance, good atmospheric corrosion resistance, good phase stability, good high temperature strength and good creep strength, as well as good workability.
[0014] US Patent No. 6,623,869 discloses a metal material consisting of 0.2% or less C, 0.01-4% Si, 0.05-2.0% Mn, 0.04% or less P, 0.015% or less S, 10-35% Cr, 30-78% Ni, 0.005-4.5% Al, 0.005-0.2% N, and one or both of 0.015-3% Cu and 0.015-3% Co, with the balance being up to 100% iron. Here, the value of 40Si+Ni+5Al+40N+10(Cu+Co) is 50 or more, and the element symbols indicate the content of the corresponding element in mass%. This material has outstanding corrosion resistance in environments where "metal dusting" may occur, and can be used for furnace tubes, tube systems, heat exchanger tubes, etc. in oil refineries and petrochemical plants, and can significantly improve the life and safety of the plants.
[0015] EP 0 508 058 A1 discloses an austenitic nickel-chromium-iron alloy consisting of (in weight percent) 0.12-0.3% C, 23-30% Cr, 8-11% Fe, 1.8-2.4% Al, 0.01-0.15% Y, 0.01-1.0% Ti, 0.01-1.0% Nb, 0.01-0.2% Zr, 0.001-0.015% Mg, 0.001-0.01% Ca, max 0.03% N, max 0.5% Si, max 0.25% Mn, max 0.02% P, max 0.01% S, and the balance including unavoidable impurities resulting from melting.
[0016] Alloys for furnace construction and the petrochemical industry must be weldable for the manufacture of the individual parts of the plant, and possibly also during installation in the plant. Due to their structure, welded seams often have low creep strength and / or a tendency to crack formation. By heat treatment of the welded seams the creep strength can be improved and the tendency to crack formation can be reduced. Some examples of the prior art are listed below:
[0017] EP 0 234 200 A1 discloses a method and an apparatus for heat treating longitudinal seam welded tubes of austenitic, ferritic or austenitic-ferritic stainless steels, the tubes being annealed after welding of the longitudinal seam. The method is characterized in that the tubes are only partially solution annealed in the area of the weld seam and heat affected zone, and the remaining areas are heat treated at a lower temperature. For highly alloyed molybdenum-containing steels, the annealing is carried out at a temperature above 1100°C, advantageously above 1250°C, and the annealing temperature is held for more than 5 seconds, advantageously about 25 seconds.
[0018] US Pat. No. 3,865,639 discloses a method for manufacturing a welded subassembly, the welded components of which are capable of withstanding service temperatures in the range of about 900-1050° C., the components being made of at least one highly alloyed austenitic steel alloyed with chromium, nickel and / or cobalt and containing less than 60% by weight iron, a maximum of 0.5% by weight carbon and small concentrations of additional elements such as manganese and silicon. In this case, the parts shown are subjected to welding, which forms at least one weld seam with a solidification front corresponding to the physical and chemical discontinuity of the seam, where this weld seam also consists of a highly alloyed austenitic steel, and is then treated in such a way that the solidification front is chemically homogenized, so that the carbides of the weld seam are present in the precipitated state to the maximum extent according to a fine and uniform distribution, as a result of which the creep strength and tensile strength of the weld seam are all increased to values at least approximately equal to those of the non-welded parts, by subjecting at least the seam and the adjacent areas of the welded parts to a homogenizing heat treatment at a temperature of about 1100-1200 ° C for a few minutes to a few hours, followed by cooling at least the seam and the adjacent areas to about 800 ° C at a cooling rate of about 100 ° C / h and then cooling to room temperature by air cooling.
[0019] US Patent No. 3,046,167 describes a method for heat treating a welded hardenable chromium-nickel stainless steel to impart a high degree of ductility and toughness to it in the hardened condition, which method includes the successive steps of welding, transforming the welded product by annealing to a structure that is substantially martensitic but contains some ferrite, and then transforming the welded product to a structure that is substantially austenitic but contains some ferrite. This is accomplished by annealing at a temperature and time sufficient to re-austenitize the martensite and ferrite and to destroy the original cast structure of the weld. Thereafter, a reverse transformation of the metal to a substantially martensitic structure, with very little ferrite, occurs, and finally, the metal is hardened by suitable heat treatment to a substantially fully martensitic condition. In fabricating a hardenable chromium-nickel-stainless steel product selected from the group of steels having analyses of about 17% chromium, 7% nickel, 1% aluminum, and balance iron; about 17% chromium, 4% nickel, 3% copper, and balance iron; about 15% chromium, 7% nickel, 2% molybdenum, 1% aluminum, and balance iron; and about 12% chromium, 8% nickel, 6% molybdenum, 1% aluminum, and balance iron, the method includes first welding the product under a shielding gas, then transforming the welded product by heating to about 760-954.4°C, cooling to about room temperature to -73.3°C, then tempering the transformed product at about 1065.6°C, then transforming the product by heating and cooling as above, and finally hardening by heating to about 482.2-593.3°C.
[0020] U.S. Pat. No. 4,168,190 describes a method and apparatus for localized solution annealing of austenitic stainless steels that have been partially sensitized, for example by a localized temperature increase, without producing a sensitized structure at the thermal boundary between the locally treated portion and the remainder of the material, the method including the steps of (a) rapidly heating the sensitized portion of the material to a temperature at which the carbides go into solution, and (b) rapidly quenching the heated material.
[0021] The problem underlying the present invention is to devise a method for producing a part with a weld seam from a wrought nickel-chromium-aluminum alloy, the part consisting in part of the wrought nickel-chromium-aluminum alloy and / or the part being installed in a plant with one or more weld seams.
[0022] The subject of the present invention is a method for manufacturing a part with one or more weld seams and / or for installing a part in a plant with one or more weld seams, the part being made of a nickel-chromium-aluminium alloy containing (in % by mass) more than 18 to 33% chromium, 1.8 to 4.0% aluminium, 0.01 to 7.0% iron, 0.001 to 0.50% silicon, 0.001 to 2.0% manganese, 0.00 to 0.60% titanium, 0.0 to 0.05% magnesium and / or calcium, respectively, 0.005 to 0.12% carbon, 0.0005 to 0.050% nitrogen, 0.0001 to 0.020% oxygen, 0.001 to 0.030% phosphorus, up to containing 0.010% sulfur, maximum 2.0% molybdenum, maximum 2.0% tungsten, balance 50% or more nickel and normal process impurities, said part consisting in whole or in part of said semi-finished nickel-chromium-aluminum wrought alloy, and after welding, only the weld seam and the heat affected zone surrounding the weld seam of said nickel-chromium-aluminum wrought alloy are subjected to an annealing at above 980°C to 1250°C for 0.05 minutes to 24 hours for homogenization and / or stress reduction of the weld seam, followed by cooling in static shielding gas or air, flowing (blast) shielding gas or air, so that the annealing improves the creep strength and creep ductility of the weld seam, Here, the following relations must be satisfied: Cr+Al≧28 (1a) and Fp≦39.9 (2a), where Fp=Cr+0.272*Fe+2.36*Al+2.22*Si+2.48*Ti+0.374*Mo+0.538*W-11.8*C (3a), Cr, Fe, Al, Si, Ti, Mo, W and C are the concentrations of the corresponding elements in mass%. is solved by the method.
[0023] Advantageous developments of the subject matter of the invention can be taken from the accompanying dependent claims.
[0024] Metal semi-finished products are, for example, semi-finished products such as plates, strips, bars, forged sections, seamless or longitudinal seam welded tubes or wire rods.
[0025] The parts can be joined from two or more machined semi-finished products and / or other parts. The joining can be performed, for example, by a fusion welding method, possibly using an additional filler metal. The filler metal can be supplied during welding, for example through a welding rod or wire. The filler metal can also consist of a part of at least one of the adjacent semi-finished products to be welded, if the geometry of the weld seam is of a corresponding shape.
[0026] The nickel-chromium-aluminium wrought alloy referred to in the present invention and abbreviated as Alloy NiCrAl-H herein is preferably melted in the open in an electric or arc furnace and then processed in a VOD (vacuum, oxidation, deoxidation) plant or a VLF (vacuum ladle furnace) plant. However, smelting and casting in a vacuum are also possible. The alloy is then cast into ingots or electrodes or cast as a continuous cast to form a precursor product. Optionally, the precursor product is then annealed at a temperature between 900 and 1270 ° C for 0.1 h to 70 h. It is also possible to remelt the alloy one or more further times in an ESR (electroslag remelting plant) and / or a VAR (vacuum arc remelting). The alloy is then introduced into the desired semi-finished product mold. For this, it is optionally annealed at a temperature between 900 and 1270 ° C for 0.1 h to 70 h, followed by hot forming, optionally with an intermediate annealing at a temperature between 900 and 1270 ° C for 0.05 h to 70 h. The surface of the material may be subjected to chemical and / or mechanical material removal processes for cleaning during and / or after hot forming (even several times). Then, if necessary, cold forming may be performed in the desired semi-finished mold with a degree of forming up to 98%, optionally with intermediate annealing at 800-1250 ° C for 0.05 min to 70 h, optionally under a shielding gas such as argon or hydrogen, followed by cooling in air, in a fluidized annealing atmosphere or in a water bath. Then, solution annealing is performed at a temperature range of 800-1250 ° C for 0.05 min to 70 h, optionally under a shielding gas such as argon or hydrogen, followed by cooling in air, in a fluidized annealing atmosphere or in a water bath. If necessary, chemical and / or mechanical cleaning of the surface of the material may be performed during and / or after the final annealing.
[0027] Preferably, the solution annealing is carried out between the following temperatures: - 1000 or >1000~1200℃ or <1200℃ - 1000 or >1000~1175℃ or <1175℃ - 1025 or >1025~1150℃ or <1150℃ - 1050 or >1050~1130℃ or <1130℃ - 1080 or >1080~1130℃ or <1130℃.
[0028] Preferably, the solution annealing is carried out for the following time intervals: - 0.05 minutes to 24 hours - 0.05 minutes to 8 hours - 0.05 minutes to 4 hours - 0.1 minutes to 1 hour - 1 minute to 1 hour - 5 minutes to 1 hour.
[0029] The wrought nickel-chromium-aluminum alloy (Alloy NiCrAl-H) used in the present invention can be successfully manufactured and used in the semi-finished forms of strip, plate, bar, forgings, wire, longitudinal seam welded tubing and seamless tubing.
[0030] These semi-finished product forms are produced with an average particle size of 30-600 μm. The preferred ranges are as follows: - 40μm~300μm - 60μm~300μm - 75μm~200μm.
[0031] The required components for the component are cut or separated from the blank, appropriately machined and then joined by a fusion welding process under shielding gas.
[0032] Alternatively, the fusion welding method may be, for example, one of the following methods: - Tungsten Inert Gas (TIG) welding - Metal Inert Gas Welding (MIG) - Metal Active Gas Welding (MAG) - Plasma welding - Electron Beam Welding - Laser Beam Welding - Gas welding or autogenous welding - Electrode welding / Manual arc welding.
[0033] The shielding gas may advantageously be argon, or argon and hydrogen, or argon and nitrogen.
[0034] However, submerged arc welding and other methods are also contemplated.
[0035] The value range of chromium element is 18-33%, and the preferred range can be adjusted as follows: - 20 or >20-33 or <33% - 22 or >22-33 or <33% - 24 or >24-33 or <33% - 24 or >24-32 or <32% - 25 or >25-32 or <32% - 26 or >26-32 or <32% - 27 or >27-32 or <32% - 28 or >28-32 or <32% - 28 or >28-31 or <31% - 28 or >28-30 or <30% - 29 or >29–31 or <31%.
[0036] The aluminum content is 1.8-4.0%, where again depending on the field of use of the alloy the preferred aluminum content can be adjusted as follows: - 1.8 or >1.8~<4.0% - 1.8 or >1.8~3.2 or <3.2% - 2.0 or >2.0~3.2 or <3.2% - 2.0 or >2.0~3.0 or <3.0% - 2.0 or >2.0~2.8 or <2.8% - 2.0 or >2.2~2.8 or <2.8% - 2.0 or >2.2-2.6 or <2.6%.
[0037] The iron content is 0.01-7.0%, and depending on the field of use, the preferred content can be adjusted within the following values: - 0.01~4.0 or <4.0% - 0.01~3.0 or <3.0% - 0.01~2.5 or <2.5% - 0.1~2.0 or <2.0% - 0.1~1.0 or <1.0%.
[0038] The silicon content is 0.001-0.50%. Preferably, Si can be adjusted in the alloy within the following ranges: - 0.001~0.20 or <0.20% - 0.001~0.10 or <0.10% - 0.001~0.05 or <0.05%.
[0039] The same is true for the element manganese, which may be present in the alloy at 0.001-2.0%. The following ranges of values are also contemplated: - 0.005~0.50 or <0.20% - 0.005~0.20 or <0.20% - 0.001~0.20 or <0.20% - 0.005~0.10 or <0.10% - 0.005~0.05 or <0.05%.
[0040] The titanium content is 0.00-0.60%. Preferably, Ti can be adjusted in the alloy within the following ranges: - 0.001~0.60 or <0.60% - 0.001~0.50 or <0.50% - 0.001~0.30 or <0.30% - 0.001~0.25 or <0.25% - 0.001~0.10 or <0.10% - 0.001~0.02 or <0.02% - 0.01-0.10 or <0.10%.
[0041] Magnesium and / or calcium are also included with a content of 0.00-0.05%. Preferably, there is the possibility to adjust these elements in the alloy as follows: - 0.00~0.03 or <0.03% - 0.00~0.02 or <0.02%.
[0042] The alloy contains 0.005 to 0.12% carbon, which can preferably be adjusted in the alloy within the following ranges: - 0.01~<0.12% - 0.01~0.10 or <0.10% - 0.01~0.08 or <0.08% - 0.01~0.05 or <0.05% - 0.02~0.10 or <0.10% - 0.03~0.10 or <0.10%.
[0043] The same applies to the nitrogen element, which is contained at a content of 0.0005 to 0.05%. The preferred content can be specified as follows: - 0.001~0.04%.
[0044] The alloy further comprises oxygen with a content of 0.0001 to 0.020%, in particular 0.0001 to 0.010%.
[0045] The alloy further comprises phosphorus with a content of 0.001 to 0.030%. The preferred content can be defined as follows: - 0.001~0.020%.
[0046] The elemental sulfur is represented in the alloy as follows: - Maximum 0.010%.
[0047] Molybdenum and tungsten, either alone or in combination, are present in the alloy in a maximum content of 2.0% each. The preferred contents can be defined as follows: - Mo max 1.0% - W max 1.0% - Mo max <1.0% - W max<1.0% - Mo max <0.50% - W max<0.50% - Mo max <0.10% - W max<0.10% - Mo max <0.05% - W max<0.05%.
[0048] Nickel is the balance. Preferably, the balance can be defined as: -> 50% or ≥ 50% -> 55% or ≥ 55% -> 60% or ≥ 60% -> 65% or ≥ 65% -> 67% or ≥ 67%.
[0049] In highly corrosive conditions, but especially to obtain good "metal dusting" resistance, it is advantageous if the following relationship between Cr and Al is satisfied: Cr+Al≧28 (1a) where chromium and aluminum are the concentrations of the respective elements in mass %. The preferred ranges can be adjusted as follows: Cr+Al≧29 (1b) Cr+Al≧30 (1c) Cr+Al≧31 (1d).
[0050] Furthermore, to provide sufficient phase stability, the following relationships must be satisfied: Fp≦39.9 (2a), where Fp=Cr+0.272*Fe+2.36*Al+2.22*Si+2.48*Ti+0.374*Mo+0.538*W-11.8*C (3a), where Cr, Fe, Al, Si, Ti, Mo, W and C are the concentrations of the corresponding elements in mass%.
[0051] The preferred ranges can be adjusted as follows: Fp≦38.4 (2b) Fp≦36.6 (2c).
[0052] Optionally, the niobium element can be adjusted to a content of 0.0-1.10% in the alloy. Preferably, the niobium can be adjusted to a content of 0.0-1.10% in the alloy within the following ranges: - 0.001~<1.10% - 0.001~1.0 or <1.0% - 0.001~0.70 or <0.70% - 0.001~0.50 or <0.50% - 0.001~0.30 or <0.30% - 0.01-0.30 or <0.30%.
[0053] If niobium is present in the alloy, a niobium term must be added to equation (3a) as follows: Fp=Cr+0.272*Fe+2.36*Al+2.22*Si+2.48*Ti+1.26*Nb+0.374*Mo+0.538*W-11.8*C (3b), where Cr, Fe, Al, Si, Ti, Nb, Mo, W and C are the concentrations of the corresponding elements in mass%.
[0054] Alternatively, the zirconium content may be 0.0-0.20%. Preferably, zirconium may be adjusted in the alloy within the following ranges: - 0.0~0.15 or <0.15% - 0.0~0.10 or <0.10% - 0.001~0.07 or <0.07% - 0.001~0.04 or <0.04% - 0.01-0.04 or <0.04%.
[0055] Optionally, the yttrium element can be adjusted to a content of 0.0-0.20% in the alloy. Preferably, the yttrium can be adjusted to the following value range in the alloy: - 0.0~0.15 or <0.15% - 0.0~0.10% or <0.10% - 0.0~0.08 or <0.08% - 0.001~<0.045% - 0.01~ 0.04 or <0.04%.
[0056] Optionally, the lanthanum element can be adjusted to a content of 0.0-0.20% in the alloy. Preferably, the lanthanum can be adjusted to a content of 0.0-0.20% in the alloy within the following ranges: - 0.0~0.15 or <0.15% - 0.0~0.10 or <0.10% - 0.0~0.08 or <0.08% - 0.001~0.04 or <0.04% - 0.01-0.04 or <0.04%.
[0057] Optionally, the cerium element can be adjusted to a content of 0.0-0.20% in the alloy. Preferably, the cerium can be adjusted to a content of 0.0-0.20% in the alloy within the following ranges: - 0.0~0.15 or <0.15% - 0.0~0.10% or <0.10% - 0.0~0.08 or <0.08% - 0.001~0.04 or <0.04% - 0.01-0.04 or <0.04%.
[0058] Optionally, when cerium and lanthanum are added simultaneously, cerium mischmetal can also be used with a content of 0.0-0.20%. Preferably, the cerium mischmetal can be adjusted in the alloy within the following ranges: - 0.0~0.15 or <0.15% - 0.0~0.10% or <0.10% - 0.0~0.08 or <0.08% - 0.001 to 0.04 or <0.04% - 0.01-0.04 or <0.04%.
[0059] Optionally, the hafnium element can be adjusted to a content of 0.0-0.20% in the alloy. Preferably, the hafnium can be adjusted to the following value ranges in the alloy: - 0.0~0.15 or <0.15% - 0.0~0.10 or <0.10% - 0.001~0.07 or <0.07% - 0.001~0.04 or <0.04% - 0.01-0.04 or <0.04%.
[0060] Optionally, 0.001-0.60% tantalum may also be included in the alloy. The preferred tantalum content may be defined as follows: - 0.001~0.50 or <0.50% - 0.001~0.40 or <0.40% - 0.001~0.30 or <0.30% - 0.001~0.20 or <0.30% - 0.001~0.10 or <0.10% - 0.01-0.10 or <0.10%.
[0061] Optionally, the element boron may be included in the alloy as follows: - Boron 0.0001-0.008%.
[0062] The preferred content can be defined as follows: - Boron 0.0005~0.008% - Boron 0.0005-0.004%.
[0063] Additionally, the alloy may optionally contain 0.0-5.0% Cobalt, which may be further limited as follows: - 0.01~5.0 or <5.0% - 0.01~2.0 or <2.0% - 0.10~2.0 or <2.0% - 0.01~0.5 or <0.5% - 0.01~0.1 or <0.1%.
[0064] Additionally, the alloy may contain up to 0.5% copper if desired.
[0065] Additionally, the copper content may be limited as follows: - Cu max <0.20 or 0.20% - Cu max <0.10 or 0.10% - Cu max <0.05 or 0.05% -Cu max<0.015%.
[0066] If copper is present in the alloy, a copper term must be added to equation (3a) as follows: Fp=Cr+0.272*Fe+2.36*Al+2.22*Si+2.48*Ti+0.477*Cu+0.374*Mo+0.538*W-11.8*C (3c) where Cr, Fe, Al, Si, Ti, Cu, Mo, W and C are the concentrations of the corresponding elements in mass%.
[0067] If niobium and copper are present in the alloy, then a term for niobium and a term for copper must be added to equation (3a) as follows: Fp=Cr+0.272*Fe+2.36*Al+2.22*Si+2.48*Ti+1.26*Nb+0.477*Cu+0.374*Mo+0.538*W-11.8*C (3d) where Cr, Fe, Al, Si, Ti, Nb, Cu, Mo, W and C are the concentrations of the corresponding elements in mass%.
[0068] Additionally, the alloy may optionally contain up to 0.5% vanadium.
[0069] Additionally, the vanadium content may be limited as follows: - V max<0.10%.
[0070] Finally, as impurities the elements lead, zinc and tin may still be present in the following contents: Lead max. 0.002% Zinc max 0.002% Tin Max 0.002%.
[0071] The annealing of the weld seams and the heat affected areas can be carried out, for example, in particular by means of heating mats, infrared radiators, lasers or inductive electrical heating.Optionally, partial regions of the remaining components can be cooled at the same time.
[0072] After welding, the entire part with the weld seam is subjected to annealing at 980-1250°C for 0.05 minutes to 24 hours in order to homogenize and / or reduce stress in the weld seam, and then cooled in static shielding gas or air, flowing (blast) shielding gas or air, so that this annealing (if necessary by solution annealing of the semi-finished product) can also improve the creep strength and creep ductility of the weld seam.
[0073] Furthermore, after the homogenization of the weld and weld seam, this annealing can be repeated, optionally by annealing the entire part with the weld seam or by annealing only the weld seam and the heat effect, in which case the sequence of partial annealing only the weld seam and the heat effect and annealing the entire part is arbitrary.
[0074] Preferably, the post-weld anneal is performed at a temperature between: - 1000 or >1000~1200 or <1200℃ - 1000 or >1000~1175 or <1175℃ - 1025 or >1025~1150 or <1150℃ - 1050 or >1050~1130 or <1130℃ - 1080 or >1080~1130 or <1130℃.
[0075] Preferably, the post-weld annealing is carried out at the following time intervals: - 0.05 minutes to 16 hours - 0.05 minutes to 8 hours - 0.05 minutes to 4 hours - 0.1 minutes to 1 hour - 1 minute to 1 hour - 5 minutes to 1 hour.
[0076] The shielding gas for post-weld annealing, if not under air, can advantageously consist of the following gases: - Argon - Argon-air mixture - Hydrogen - Argon-hydrogen mixed gas - Argon-nitrogen gas mixture.
[0077] The improvement in creep strength and creep ductility of the weld seam occurs especially in the range of gamma prime formation, which includes the temperature range below 750°C.
[0078] After annealing a part with a weld seam, or after annealing only the weld seam and heat effects of a part, or after annealing the weld seam and heat effects from the plant installation state, the surface can optionally be cleaned or machined by brushing, pickling, blasting, grinding, turning, stripping and / or milling. One or more of these machining operations can also optionally be carried out already after welding. In particular, material-removing machining after the final annealing by grinding, turning, stripping and milling improves the corrosion resistance, especially the "metal dusting" resistance, of the annealed surface, especially of the weld seam and heat effects.
[0079] After polishing the weld seams and heat affected parts, it is advantageous to achieve roughness values Ra of 0.01 to 15 μm, since this increases the corrosion resistance, in particular the metal dusting resistance, which rises approximately to the value of the base material.
[0080] The parts manufactured according to the invention are preferably used in areas where highly corrosive conditions prevail, such as for example strong carburizing conditions, atmospheres which cause "metal dusting", as is the case for parts in the petrochemical industry, and are furthermore also suitable for furnace construction. [Brief description of the drawings]
[0081] [Figure 1a] On the left side are schematic top and cross-sectional views of semi-finished products such as sheet, strip 2, bar 3, tube 4 and wire or filler metal in wire form 5, and on the right side are diagrams illustrating an exemplary production of a part 7 by chamfering two sheets 1a, 1b and joining them by fusion welding with the filler metal in wire form 5 using a V-groove joint 6a. [Figure 1b]3 shows an exemplary production of a part 7. On the left side, chamfering of the ends 4a, 4b of two tubes and joining by fusion welding with a filler material 5 in wire form using a V-groove seam 6b. In the middle, drilling of a plate 1c by milling, inserting a tube 4c and joining by fusion welding with a filler material 5 in wire form using a fillet weld 6c. On the right side, butt joining 6d of two strip pieces 2a, 2b with machined matching edges, with a filler material 9 at a portion of the edges. [Diagram 2] Figure 1 shows metal loss due to "metal dusting" versus aluminum and chromium content in a strongly carburizing gas with 37% CO, 9% H2O, 7% CO2, 46% H2 and the following activities ac=163, p(O2)=2.5×10-27 (from Hermse, CGM and van Wortel, JC: Metal dusting: relationship between alloy composition and degradation rate. Corrosion Engineering, Science and Technology 44 (2009), p. 182-185). [Diagram 3] FIG. 1 is a diagram showing the quantitative ratio of phases in thermodynamic equilibrium with respect to temperature for Alloy 690 (N06690) in an example of batch 111389. [Figure 4] FIG. 2 is a diagram showing the quantitative ratio of phases in a thermodynamic equilibrium state versus temperature for Alloy 693 (N06693) in the example of Alloy 3 in Table 2. [Diagram 5] FIG. 2 is a diagram showing the quantitative ratio of phases in a thermodynamic equilibrium state versus temperature for Alloy 693 (N06693) in the example of Alloy 10 in Table 2.
[0082] Working Example: Parts manufacturing from semi-finished products The left side of Fig. 1a shows a schematic top view and a cross section of a semi-finished product in the form of a sheet (1), a strip (2), a bar (3), a tube (4), a wire or a filler material in the form of a wire (5). The right side of Fig. 1a illustrates a method of forming a product or a precursor product (7), for example by cutting two parts (1a, 1b) from a sheet semi-finished product, chamfering (ii) and then joining (iv) them by fusion welding (iii) with a filler material in the form of a wire (5) using a V-groove (6a). The left side of Fig. 1b shows a further example of forming a product or a precursor product (7), for example by cutting two tube parts (4a, 4b) from a tube semi-finished product, chamfering (ii) and then joining (iv) with a filler material in the form of a wire (5) using a V-groove (6b). The center of Fig. 1b shows a further example of the formation of a product or precursor product (7) in which a hole is milled (ii) through a plate blank or part (1c) into which a tube blank or part (3c) is inserted and which is joined (iv) by fusion welding (iii) with a filler metal in the form of a wire (5) using a fillet weld (6c). The right side of Fig. 1b shows a further example of the formation of a product or precursor product (7) in which two strip pieces (2a, 2b) separated (ii) from the strip blank are machined to match their edges and are butt-joined (6d) (iv) by fusion welding (iii) with a filler metal (9) on part of the edges.
[0083] Testing: The equilibrium phases formed for the various alloy modifications were calculated using the JMatPro program from Thermotech, Inc. The Thermotech nickel alloy database TTNI7 was used as the calculation database.
[0084] The creep strength is determined in an uninterrupted uniaxial creep test with extension measurement under tensile stress according to DIN EN ISO 204. For this, the specimen is mounted in a creep testing machine and loaded with a constant test force. Here, the time to rupture t u and creep rupture elongation A ub The rupture time is an index of creep strength, and the creep rupture elongation is an index of creep ductility. The test is performed with a diameter of 10 mm in the measurement range and an initial reference length L r0 The measurements were carried out on 50 mm circular specimens. The sampling was carried out transversely to the forming direction of the semi-finished product.
[0085] Description of characteristics The nickel-chromium-aluminum alloy used in the present invention, Alloy NiCrAl-H, exhibits excellent corrosion resistance under highly corrosive conditions, including, for example, excellent "metal dusting" resistance, good phase stability and good creep strength.
[0086] phase stability In the nickel-chromium-aluminium-iron system with the addition of titanium and / or niobium, various embrittled TCP phases (Topologically Closed Packed Phases) can occur, depending on the alloy content, such as Laves, sigma, or μ phases, or even embrittled η or ε phases. For example, in the case of N06690, batch 111389 (see Table 2 for the composition used here), the equilibrium phase ratios were calculated as a function of temperature, with a maximum of 720°C (T s BCC It has been mathematically shown that below the temperature T , a large quantitative proportion of α-chromium (BCC phase in Figure 3) is formed. This phase is analytically very different from the base material, so its formation is generally difficult. However, the formation temperature T s BCCIf T is very high, this phase can well occur, as described for example for UNS 06693, a variant of Alloy 693, in “E. Slevolden, JZ Albertsen. U. Fink, “Tjeldbergodden Methanol Plant: Metal Dusting Investigations, “Corrosion / 2011, paper no. 11144 (Houston, TX: NACE 2011), p. 15”. Figures 4 and 5 show the phase diagrams of Alloy 3, a variant of Alloy 693 (U.S. Pat. No. 4,882,125, Table 1), and Alloy 10 of Table 2. This phase is brittle and leads to undesirable embrittlement of the material. Alloy 3 has a formation temperature T of 1079°C. s BCC Alloy10 has a formation temperature T of 939°C. s BCC "E. Slevolden, JZ Albertsen. U. Fink, Tjeldbergodden Methanol Plant: Metal Dusting Investigations, "Corrosion / 2011, paper no. 11144 (Houston, TX: NACE 2011), p. 15" does not provide a precise analysis of the alloys at which α-chromium (BCC) forms. However, the examples given for Alloy 693 in Table 2 and the formation temperature T s BCC From the analytical material with the highest calculated temperature (e.g., Alloy 10), it is assumed that α-chromium (BCC phase) may form. s BCCIn the case of the alloy with a lowered temperature of 1000°C (1000°F), α-chromium was observed only near the surface in “E. Slevolden, JZ Albertsen. U. Fink, Tjeldbergodden Methanol Plant: Metal Dusting Investigations, “Corrosion / 2011, paper no. 11144 (Houston, TX: NACE 2011), p. 15”. In order to avoid the occurrence of such embrittled phases, the nickel-chromium-aluminum alloy (Alloy NiCrAl-H) used in the present invention is formed at a temperature of 1000°C (1000°F). s BCC However, the lowest formation temperature T s BCC It is desirable for the temperature to be at or below 939°C.
[0087] This is especially the case when the following equation is satisfied: Fp≦39.9 (2a), where Fp=Cr+0.272*Fe+2.36*Al+2.22*Si+2.48*Ti+1.26*Nb+0.477*Cu+0.374*Mo+0.538*W-11.8*C (3d), where Cr, Al, Fe, Si, Ti, Nb, Cu, Mo, W and C are the concentrations of the respective elements in mass percent. Table 2 of the alloys shows that for Alloy 8, Alloy 3 and Alloy 2, Fp is greater than 39.9, and for Alloy 10, it is just 39.9. For all other alloys, T s BCC is less than 939°C, so Fp<39.9.
[0088] Examples of the manufacture of parts with welded seams and their properties Tables 3a and 3b show the analysis of industrially smelted batches of the alloy Alloy NiCrAl-H used in the present invention, from which plates and welding rods (filler metal in the form of wire) were produced. For these batches, the formula (2a) Al+Cr≧28 is fulfilled, and therefore the requirements imposed for "metal dusting" resistance are also fulfilled. For the compositions in Tables 3a and 3b, the value of Fp was also calculated according to formula (3a). As required, Fp is less than 39.9.
[0089] These batches were smelted in the open in quantities of 16 tons and then processed in a VOD plant. Electrodes were then cast and remelted in an ESR. The alloys were then annealed at temperatures between 900 and 1270 °C for 0.1-70 h and hot formed, with intermediate annealing at temperatures between 900 and 1270 °C for 0.1-70 h. From batch 319144, hot-rolled plates with thicknesses of 25 mm and 16 mm were produced. From batch 318385, hot-rolled wire rods were produced. After hot rolling, the plates were solution annealed at 1100 °C for 40 min and then cooled in air. They were then blasted, pickled and polished to remove the oxide layer. The grain size of the 25 mm thick plates was about 89 μm, and the grain size of the 16 mm thick plates was about 82 μm. Thus, the grain sizes of the 25 mm and 16 mm thick plates are comparable. The rolled wire was similarly blasted, pickled and polished, then intermediate annealed at 800 to 1250°C for 0.05 minutes to 70 hours, and cold drawn to the final thickness. The wire was then solution annealed in a hydrogen atmosphere at a temperature range of 800 to 1250°C for 0.05 minutes to 70 hours, and processed into a welding rod having a diameter of 2.0 to 2.4 mm.
[0090] Sheet pieces were cut from the solution-annealed semi-finished sheets 25 mm thick, annealed at 980 °C for 3 h and then cooled in air. Creep test specimens were prepared transverse to the rolling direction from sheets or sheet pieces that had only been solution-annealed and from sheets or sheet pieces that had been further annealed. Table 5 shows the results of the creep tests according to DIN EN ISO 204.
[0091] Plate pieces measuring 150 x 500 mm were cut from the 16 mm thick plate blanks. Two of each were welded by manual TIG welding under pure argon with a 70° V-groove seam, using 2.0 mm and 2.4 mm thick welding rods of batch 318385 as filler metal, with the welding parameters shown in Table 4. The weld seam and the heat affected area were brushed immediately after welding. Some of the welded plate pieces thus produced were annealed at 980 °C for 3 h and then air cooled, others were annealed at 1100 °C for 40 min and then air cooled, and still others were annealed at 1100 °C for 3 h and then air cooled. Some were not annealed. Seams or parts of seams were also produced with grinding or without any subsequent machining. Creep test specimens were prepared from the welded plates and from the welded and annealed plates or plate pieces, transverse to the weld seam. Table 5 shows the results of creep tests according to DIN EN ISO 204.
[0092] From Table 5, in the creep test at 600°C, the solution-annealed plate material that was additionally annealed at 980°C for 3 hours and then air-cooled (samples 19 45B and 19 46B) had a longer fracture time t than the plate material that was only solution-annealed (samples 19 23B and 19 7B). u It can be seen that the creep test (specimens 302W and 303W) performed transversely to the weld seam without further annealing (Prior Art T) also showed a reduction in the rupture time t u It was found that the time to fracture t was significantly shortened. When the welded specimens from which the creep specimens were prepared were additionally annealed at 980°C for 3 hours and then air-cooled (specimens 247W and 249W), the time to fracture t u There is no significant effect on creep rupture elongation A u b In contrast, when the welded specimens from which the creep samples were prepared were subjected to the additional annealing according to the present invention at 1100°C for 40 minutes and then air-cooled (samples 250W and 503W), the rupture time t u The creep rupture elongation A u bIn particular, when the welded specimens from which creep samples were prepared were subjected to additional annealing according to the present invention at 1100°C for 3 hours and then air-cooled (specimens 511W and 506W), the rupture time t u is further extended, and the creep rupture elongation A u b The creep strength also increases and reaches almost the same value as that of the plate materials (samples 1923B and 197B) that were not welded after only solution annealing.
[0093] At 700°C, creep tests (specimen 306W) performed transversely to the weld seam without further annealing (Prior Art T) also showed a shorter rupture time t compared to creep tests on plate material (specimen 3034B) that had only been solution annealed, as in the case of 600°C. u It was found that the time to fracture was shortened when the welded part from which the creep specimen was prepared was additionally annealed at 980°C for 3 hours and then air-cooled (specimen 248W) compared with specimen 306W which was not annealed after welding. u In contrast, when the welded specimen from which the creep specimen was prepared was subjected to the additional annealing according to the present invention at 1100°C for 40 minutes and then air-cooled (specimen 251W), the rupture time t u is approximately doubled, and the creep rupture elongation A u b In particular, when the welded specimen from which the creep specimen was prepared was subjected to additional annealing at 1100°C for 3 hours according to the present invention and then air-cooled (specimen 253W), the fracture time t u However, the rupture time in the creep test of the plate material that had been subjected to only solution annealing is further extended.
[0094] At 800°C, the plate material that had been solution annealed and then additionally annealed at 980°C for 3 hours and then air-cooled (sample 19 49B) had a longer fracture time t compared to the plate material that had only been solution annealed (sample 19 22B). uThe creep test (specimen 309W) performed transversely to the weld seam without further annealing (Prior Art T) also showed a significantly shorter rupture time t u The time to fracture t was also approximately the same when the welded specimen from which the creep specimen was prepared was additionally annealed at 1100°C for 40 minutes and then air-cooled (specimen 519W) compared with the creep test of the plate material that had only been solution annealed (specimen 1922B). u are about the same.
[0095] This means that by heat treating the weld seam after welding at 1100°C for at least 40 minutes, according to the invention, the rupture time and creep rupture elongation of creep specimens transverse to the weld seam are significantly improved at temperatures of 600°C and 700°C, thus at temperatures in the range of γ' formation. Above the γ'-solvus temperature, the weld seam without annealing has a rupture time t u Annealing the weld seam has little effect on the time to rupture at service temperatures above the γ'-solvus.
[0096] The claimed limits for the method and for the nickel-chromium-aluminium alloy used therein, Alloy NiCrAl-H, can therefore be justified in detail as follows: Too low a chromium content means that when the alloy is used in corrosive atmospheres, the chromium concentration below the oxide layer falls below a critical limit so quickly that a closed chromium oxide layer can no longer form. Therefore, 18% chromium is the lower chromium limit. Too high a chromium content deteriorates the phase stability of the alloy, especially at a high aluminum content of 1.8%. Therefore, 33% chromium should be considered as the upper limit.
[0097] When an aluminum oxide layer forms under the chromium oxide layer, the oxidation rate decreases. If the aluminum content is less than 1.8%, the aluminum oxide layer is too incomplete to fully exert its effect. If the aluminum content is too high, the workability of the alloy is impaired. Therefore, the aluminum content is limited to 4.0%.
[0098] The cost of the alloy increases with decreasing iron content. Below 0.01%, the need to use special precursor materials increases the costs disproportionately. For cost reasons, 0.01% iron should therefore be considered as a lower limit. With increasing iron content, the phase stability decreases (formation of embrittled phases), especially at high chromium and aluminum contents. Therefore, 7% iron is a practical upper limit to ensure the phase stability of the alloy according to the invention.
[0099] Silicon is necessary for the production of the alloy. Therefore, a minimum content of 0.001% is required. Too much silicon impairs the workability and phase stability, especially at high aluminum and chromium contents. Therefore, the silicon content is limited to 0.50%.
[0100] A minimum content of 0.001% manganese is required to improve workability. Manganese is limited to 2.0% because this element reduces oxidation resistance.
[0101] Titanium increases high temperature strength. Above 0.60%, oxidation behavior may deteriorate, so 0.60% is the maximum value.
[0102] Even with very low magnesium and / or calcium contents, the machinability is improved by the binding of sulfur, thereby avoiding the formation of low-melting NiS eutectic. If the content is too high, intermetallic Ni-Mg or Ni-Ca phases may form, which also significantly impair the machinability. Therefore, the magnesium and / or calcium contents are limited to a maximum of 0.05%.
[0103] A minimum carbon content of 0.005% is necessary to obtain good creep resistance. Carbon is limited to a maximum of 0.12%, because above this content this element reduces workability due to the excessive formation of primary carbides.
[0104] A minimum content of 0.0005% nitrogen is required, which improves the workability of the material. Nitrogen is limited to a maximum of 0.05%, since this element reduces the workability by forming coarse carbonitrides.
[0105] To ensure the manufacturability of the alloy, the oxygen content must be ≦0.020%. Too little oxygen content increases the cost. Therefore, the oxygen content is ≧0.0001%.
[0106] The phosphorus content is preferably less than 0.030%, because this surface active element impairs oxidation resistance. Too little phosphorus increases the cost. Therefore, the phosphorus content is ≧0.001%.
[0107] It is desirable to adjust the sulfur content as low as possible, since this surface active element impairs oxidation resistance, so a maximum of 0.010% sulfur is specified.
[0108] Molybdenum is limited to a maximum of 2.0% since this element reduces oxidation resistance.
[0109] Tungsten is limited to a maximum of 2.0% since this element also reduces oxidation resistance.
[0110] The remaining element is nickel. Too little nickel reduces the phase stability, especially when the chromium content is high. Therefore, nickel must be at least 50%.
[0111] In highly corrosive conditions, but especially to obtain good "metal dusting" resistance, it is advantageous if the following relationship between Cr and Al is satisfied: Cr+Al≧28 (1a) where Cr and Al are the concentrations of the respective elements in mass %. Only then is the content of oxide-forming elements high enough to guarantee sufficient "metal dusting" resistance.
[0112] Furthermore, to provide sufficient phase stability, the following relationships must be satisfied: Fp≦39.9 (2a), where Fp=Cr+0.272*Fe+2.36*Al+2.22*Si+2.48*Ti+0.374*Mo+0.538*W-11.8*C (3a), where Cr, Fe, Al, Si, Ti, Mo, W and C are the concentrations of the respective elements in mass %. The limits of Fp and the possibility of incorporation of further elements have been explained in detail in the previous text.
[0113] If necessary, the oxidation resistance can be further improved by the addition of oxygen-affinity elements such as yttrium, lanthanum, cerium, cerium mischmetal, zirconium, and hafnium, which do this by being incorporated into the oxide layer where they block the diffusion paths of oxygen at the grain boundaries.
[0114] Yttrium increases oxidation resistance. For cost reasons, the upper limit is set at 0.20%.
[0115] Lanthanum improves oxidation resistance. For cost reasons, the upper limit is set at 0.20%.
[0116] Cerium increases oxidation resistance. For cost reasons, the upper limit is set at 0.20%.
[0117] Cerium mischmetal increases oxidation resistance. For cost reasons, the upper limit is set at 0.20%.
[0118] Niobium can also be added as needed to increase high temperature strength. Higher contents result in very high costs. Therefore, the upper limit is set at 1.10%.
[0119] If desired, the alloy may also contain tantalum, since it also improves high temperature strength and oxidation resistance. Higher contents are very cost-prohibitive. Therefore, the upper limit is specified at 0.60%. A minimum content of 0.001% is required to be effective.
[0120] Optionally, the alloy may also contain zirconium, which enhances high temperature strength and oxidation resistance. For cost reasons, the upper limit is set at 0.20% zirconium.
[0121] Optionally, the alloy may also contain hafnium, which enhances high temperature strength and oxidation resistance. For cost reasons, the upper limit is set at 0.20% hafnium.
[0122] Boron can be added to the alloy if necessary, since it improves creep resistance. Therefore, it is desirable for it to have a content of at least 0.0001%. At the same time, this surface active element worsens oxidation resistance. Therefore, boron is specified as a maximum of 0.008%.
[0123] Cobalt may be present in this alloy at a maximum content of 5.0%, as higher contents significantly reduce the oxidation resistance.
[0124] Copper is limited to a maximum of 0.5% since this element reduces oxidation resistance.
[0125] Vanadium is limited to a maximum of 0.5% since this element reduces oxidation resistance.
[0126] Lead is limited to a maximum of 0.002% because this element reduces oxidation resistance, as are zinc and tin.
[0127] If the grain size is too small, below 30 μm, the creep strength at high temperatures is poor, whereas if the grain size is too large, above 600 μm, the creep ductility in the temperature range of gamma prime formation is very low.
[0128] Annealing above 980°C to 1250°C for 0.05 minutes to 24 hours for homogenization and / or stress reduction of the weld seam, followed by cooling in static shielding gas or air, flowing (blast) shielding gas or air, improves the creep strength and creep ductility of the weld seam in the range of gamma' formation. At temperatures below 980°C, homogenization cannot be carried out economically because the time required for homogenization is too long due to the temperature being too low. At temperatures significantly higher than solution annealing, significant grain growth occurs, which reduces the high-temperature strength at low temperatures and also reduces the elongation in creep tests in the range of gamma formation. At short times of less than 0.05 minutes, even very high temperatures are not sufficient. Times of more than 24 hours are uneconomical, especially for large parts.
[0129] Annealing under shielding gas reduces the oxidation of the material during annealing, thus reducing material loss. [Table 1] [Table 2] [Table 3] [Table 4] [Table 5] [Table 6]
Claims
1. 1. A method for manufacturing a part with one or more weld seams and / or for installing a part in a plant with one or more weld seams, said part consisting of a nickel-chromium-aluminium alloy containing (in % by weight) more than 18 to 33% chromium, 1.8 to 4.0% aluminium, 0.01 to 7.0% iron, 0.001 to 0.50% silicon, 0.001 to 2.0% manganese, 0.00 to 0.60% titanium, 0.0 to 0.05% magnesium and / or calcium, respectively, 0.005 to 0.12% carbon, 0.0005 to 0.050% nitrogen, 0.0001 to 0.020% oxygen, 0.001 to 0.030% phosphorus, max. 0.010% sulphur, max 2.0% molybdenum, max 2.0% tungsten, balance 50% or more nickel and normal process impurities, said part or all consisting of said semi-finished nickel-chromium-aluminum wrought alloy, and after welding, only said weld seam and the heat affected zone surrounding said weld seam of said wrought nickel-chromium-aluminum alloy are subjected to annealing at above 980-1250°C for 0.05 minutes to 24 hours for homogenization and / or stress reduction of said weld seam, followed by cooling in static shielding gas or air, flowing (blast) shielding gas or air, so that said annealing improves the creep strength and creep ductility of said weld seam; Here, the following relations must be satisfied: Cr+Al≧28 (1a) and Fp≦39.9 (2a), where Fp=Cr+0.272*Fe+2.36*Al+2.22*Si+2.48*Ti+0.374*Mo+0.538*W−11.8*C (3a), Cr, Fe, Al, Si, Ti, Mo, W and C are the concentrations of the corresponding elements in mass%. method.
2. 2. The method of claim 1, wherein the part has a weld seam, and after the welding, the entire part with the weld seam is subjected to a further annealing at above 980°C to 1250°C for 0.05 minutes to 24 hours for homogenization and / or stress reduction of the weld seam, and then cooled in static shielding gas or air, flowing (blast) shielding gas or air or in water, so that the creep strength and creep ductility of the weld seam are improved.
3. 3. The method according to claim 1 or 2, wherein after the polishing process of the weld seam and the heat application part, a roughness value Ra of 0.01 to 15 μm is advantageously achieved, since this increases the corrosion resistance, in particular the "metal dusting" resistance, which rises approximately to the value of the base material.
4. The method according to any one of claims 1 to 3, wherein the semi-finished product has a particle size of 30 to 600 μm.
5. 5. The method according to claim 1, wherein the chromium content is from 20 to 33%.
6. 6. The method according to claim 1, wherein the aluminum content is between 1.8 and 3.2%.
7. 7. The method according to claim 1, wherein the iron content is from 0.01 to 4.0%.
8. Optionally the niobium content is 0.0 to 1.1%, where the Nb term is added to equation (4a): Fp=Cr+0. 272*Fe+2. 36*Al+2. 22*Si+2. 48*Ti+1. 26*Nb+0. 374*Mo+0. 538*W-11. 8*C (3b), 8. The method of claim 1, wherein Cr, Fe, Al, Si, Ti, Nb, Mo, W and C are the concentrations of the elements in mass %.
9. 9. The method of any one of claims 1 to 8, optionally with a zirconium content of 0.0 to 0.20%.
10. 10. The method of claim 1, wherein optionally the yttrium content is between 0.001 and 0.20%.
11. 11. The method of any one of claims 1 to 10, optionally with a lanthanum content of 0.001 to 0.20%.
12. 12. The method of any one of claims 1 to 11, optionally with a cerium content of 0.001 to 0.20%.
13. 13. The process according to any one of claims 1 to 12, optionally with a cerium mischmetal content of 0.001 to 0.20%.
14. 14. The method of any one of claims 1 to 13, optionally with a hafnium content of 0.001 to 0.20%.
15. 15. The method of any one of claims 1 to 14, optionally with a tantalum content of 0.001 to 0.60%.
16. 16. The method of any one of claims 1 to 15, optionally with a boron content of 0.0001 to 0.008%.
17. The method of any one of claims 1 to 16, further optionally comprising 0.0 to 5.0% cobalt.
18. and optionally up to 0.5% copper, where a Cu term is added to equation (4a) to give: Fp=Cr+0.272*Fe+2.36*Al+2.22*Si+2.48*Ti+0.477*Cu+0.374*Mo+0.538*W-11.8*C (3c), 18. The method of any one of claims 1 to 17, wherein Cr, Fe, Al, Si, Ti, Cu, Mo, W and C are the concentrations of the elements in mass %.
19. 19. The method of any one of claims 1 to 18, further optionally comprising up to 0.5% vanadium.
20. 20. The method according to any one of claims 1 to 19, wherein the impurities are adjusted to a content of max. 0.002% Pb, max. 0.002% Zn, max. 0.002% Sn.
21. 21. Use of the method according to any one of claims 1 to 20 in the petrochemical industry.
Citation Information
Patent Citations
Metal material having metal dusting resistance
JP2003073763A
Nickel-chromium-aluminum alloy with good workability, creep strength, and corrosion resistance.
JP2015524023A
Welding structure of heat-resistant pipe
JP2016132019A
Austenitic heat-resistant alloy weld joint
JP2021167439A
Nickel-chromium-iron-aluminum alloy with excellent workability, creep strength and corrosion resistance and use thereof
JP2023504842A